The Flamboyant Rooster and other Tshivenda Song Stories, Edited by Jaco Kruger and Ina le Roux, Illustrated by Deon Coetzer, School of Music, North-West University, Potchefstroom: South Africa. 149 pages. - McConnachie, Boudina (International Library of African Music, 2008)
pages: 122-123
Keywords: South Africa; African Music